Green Synthesis and Antibacterial Activity of Silver Nanoparticles using Turi (Sesbania grandiflora Lour) Leaf Extract - Wilda Amananti; Aldi Budi Riyantal; Kusnadi Kusnadi; Kawther Ameen Muhammed Saeed Aledresi (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
Research has been carried out on the ability of antibacterial activity with using Ag nanoparticles with a variation of the AgNO3 mole ratio of 0.5 mM and 1.5 mM as much as 90 ml and the amount of turi leaf extract added 1 mL. The material was characterized by UV-vis spectroscopy. Determination of antibacterial activity was carried out through Escherichia coli bacteria after interacting with nanoparticles Ag. Green synthesis of silver nanoparticles can be carried out using an aqueous extract of turi leaves, with the optimum concentration of 0.5 mM AgNO3 and 1.5 mM AgNO3 being synthesized for one day at room temperature. Resulting in silver nanoparticles with energy band gap values of 3.9 eV and 3.88 Ev having antibacterial activity of Escherichia coli with inhibitory power of 5.52 mm and 6.65 mm, respectively.